2020
DOI: 10.3390/antiox9030249
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Antioxidant Potential of Seaweed Extracts for Enrichment of Convenience Food

Abstract: In recent years, there has been a growing interest in natural antioxidants as replacements of synthetic compounds because of increased safety concerns and worldwide trend toward the usage of natural additives in foods. One of the richest sources of natural antioxidants, nowadays largely studied for their potential to decrease the risk of diseases and to improve oxidative stability of food products, are edible brown seaweeds. Nevertheless, their antioxidant mechanisms are slightly evaluated and discussed. The a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
53
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(53 citation statements)
references
References 42 publications
0
53
0
Order By: Relevance
“…PT extracts showed low DPPH free radical scavenging activity although total polyphenol content was high amount. Corsetto et al [ 37 ] have previously reported that high content of total polyphenols provides anti-inflammatory activities via scavenging reactive oxygen species (ROS) or cellular endogenous defenses via enhancing antioxidant, while showing the low antioxidant capability in DPPH radical scavenging activity. Previously, we have reported that the yield rate of PT extracts was 13% and the concentration of porphyra-334 in this PT extracts was 68.45 ± 20% mg/g [ 17 ].…”
Section: Resultsmentioning
confidence: 99%
“…PT extracts showed low DPPH free radical scavenging activity although total polyphenol content was high amount. Corsetto et al [ 37 ] have previously reported that high content of total polyphenols provides anti-inflammatory activities via scavenging reactive oxygen species (ROS) or cellular endogenous defenses via enhancing antioxidant, while showing the low antioxidant capability in DPPH radical scavenging activity. Previously, we have reported that the yield rate of PT extracts was 13% and the concentration of porphyra-334 in this PT extracts was 68.45 ± 20% mg/g [ 17 ].…”
Section: Resultsmentioning
confidence: 99%
“…Seeds and nuts, fruits, and seaweed have considered anti-inflammatory food ingredients [ 38 , 44 , 45 , 46 ]. There is growing acceptance that inflammation could play a role in ARHL [ 16 , 19 , 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Currently, there is an increasing interest in natural antioxidants as an alternative to synthetic compounds, due to safety concerns and a worldwide trend of using natural food additives [1,2]. Indeed, natural antioxidants can shield the human body from free radicals or other reactive oxygen species and prevent or detain the development of many chronic diseases such as cancer, diabetes or atherosclerosis [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…Seaweed is a rich source of antioxidants, which has received considerable attention from researchers, consumers and food industries [12]. Under severe environmental conditions, these macroalgae develop unique metabolic processes to survive, resulting in the synthesis of a wide range of secondary metabolites, some of which are antioxidant peptides [1].…”
Section: Introductionmentioning
confidence: 99%